Will AI Enable the Era of Human-Animal Organ Transplants? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Will AI Enable the Era of Human-Animal Organ Transplants? The global organ shortage represents one of the most critical challenges in modern medicine. T...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning